Bilayer Type I Atelocollagen Scaffolds for In Vivo Regeneration of Articular Cartilage Defects - Sang Hun Woo; Bo Keun Lee; Andrew S. Kwak; Jin Hyo Yang; Seo Yeon Kim; Man Soo Kim; Ji Chul Yoo (Bioengineering)
Articular cartilage has limited regenerative potential due to its anatomical characteristics, making complete recovery from damage challenging. Microfracture (MFx) is a widely used technique to promote cartilage healing, often enhanced with scaffolds to improve outcomes. In this study, we compared the efficacy of bilayer atelocollagen and standard collagen scaffolds combined with MFx in treating osteochondral defects in a rabbit model. Three articular cartilage defects were created in the femoral condyle of each rabbit and treated with either MFx plus a bilayer atelocollagen scaffold (test group), MFx plus a standard collagen scaffold (positive group), or MFx alone (negative group). Macroscopic and histological assessments were performed at 3, 6, and 12 weeks. By week 12, macroscopic examination showed hyaline-like cartilage restoration in the test group, while the positive group exhibited restoration with some overgrowth, and the negative group showed no restoration. Histological analysis revealed significantly better restoration in the test group than in the negative group, with comparable outcomes between the test and positive groups. These findings suggest that bilayer atelocollagen scaffold implantation following MFx is a promising treatment for articular cartilage defects and may provide a viable therapeutic option for patients with cartilage damage.